Succinate Dehydrogenase B Subunit Immunohistochemical Expression Predicts Aggressiveness in Well Differentiated Neuroendocrine Tumors of the Ileum - Milione, Massimo (MDPI, 2012)
Immunohistochemical loss of the succinate dehydrogenase subunit B (SDHB) has recently been reported as a surrogate biomarker of malignancy in sporadic and familial pheocromocytomas and paragangliomas through the activation of hypoxia pathways. However, data on the prevalence and the clinical implications of SDHB immunoreactivity in ileal neuroendocrine tumors are still lacking. Thirty-one consecutive, advanced primary midgut neuroendocrine tumors and related lymph node or liver metastases from 24 males and seven females were immunohistochemically assessed for SDHB. All patients were G1 tumors (Ki-67 labeling index ≤2%). SDHB immunohistochemistry results were expressed as immunostaining intensity and scored as low or strong according to the internal control represented by normal intestinal cells. Strong positivity for SDHB, with granular cytoplasmatic reactivity, was found in 77% of primary tumors (T), whilst low SDHB expression was detected in 90% of metastases (M). The combined analysis (T+M) confirmed the loss of SDHB expression in 82% of metastases compared to 18% of primary tumors. SDHB expression was inversely correlated with Ki-67 labeling index, which accounted for 1.54% in metastastic sites and 0.7% in primary tumors. A correlation between SDHB expression loss, increased Ki-67 labeling index and biological aggressiveness was shown in advanced midgut neuroendocrine tumors, suggesting a role of tumor suppressor gene.